CLASSROOM MANAGEMENT DALAM EDUKASI HADIS QUDSI: (Studi Kasus di Langgar Kidul Al-Muhajirin Sukodono Sidoarjo) - Irfan Yuhadi; Nurul Budi Murtini (Sekolah Tinggi Dirasat Islamiyah Imam Syafi'i Jember, 2024)
In the teaching and learning process there is education and classroom management. Classroom management is a process of activities in organizing a class systematically, which can take the form of preparing facilities and infrastructure, arranging study rooms, creating a conducive situation in learning, with the aim of providing class comfort in learning so that learning objectives can be achieved effectively and efficiently. As for hadith qudsi education is teaching and educating others about the hadith qudsi narrated by the Prophet Muhammad (peace be upon him). There are around 286 prayer rooms (musala) in the Sukodono sub-district area, one of which is Langgar Kidul Sukodono. The aim of this research is to analyze and find the implementation and indicators of the classroom management effectiveness in hadith qudsi education in Langgar Kidul Al-Muhajirin Sukodono Sidoarjo. The approach in this research is to use a qualitative approach with a case study type. The results of this research show that the implementation of classroom management in hadith qudsi education in Langgar Kidul Sukodono Sidoarjo are; (1) the desire to know the word of Allah in hadith qudsi, (2) preparing teaching materials for hadith qudsi, (3) reading hadith qudsi and explaining it interestingly, (4) delivering the material without rushing and repeating it, (5) providing a screen monitors in women’s classroom, (6) there is food to make studying more comfortable and (7) question and answer sessions in women’s classroom are sometimes a bit less conducive.